The Communication Patterns Between Parents And Migrant Children in The Digital Era: Strengthening Emotional Connections Through Technology - Celvin Yhosep Sinaga; Aholiab Watloly; Simona Christina Henderika Litaay (Baileo)
This study aims to analyze the communication patterns between parents and migrant children in the digital era, as well as the impact on their emotional connection. Digital technology provides opportunities for parents and children to stay connected despite physical distance, but the frequency of communication plays a crucial role in shaping the quality of that relationship. The research was conducted on migrant students living in the dormitories of Pattimura University using a qualitative approach. Data collection techniques included observation, in-depth interviews, and documentation. The results indicate that migrant children who frequently communicate with their parents feel more emotionally connected, less lonely, and are able to develop independence and new experiences. Conversely, students with less frequent communication tend to feel lonelier but use this as a coping strategy to stay focused on their life away from home. Some students expressed that overly frequent communication with their parents triggered excessive longing and a desire to return home. The novelty of this research lies in understanding how digital technology serves not only as a communication tool but also as an emotional connector in families separated by distance. This study recommends that future research delve deeper into the psychological and social aspects of communication frequency and its impact on the emotional well-being of migrant children. The findings contribute to the development of social sciences and humanities, particularly in understanding family communication dynamics in the digital era.